Ultradelayed Arterial Thrombosis: Critical Flap Ischemia After Phalloplasty. Issue 2 (February 2021) - Smith, Jesse R.; Teven, Chad M.; Choudry, Umar; Gottlieb, Lawrence J.
Abstract : Background and Objectives: Delayed arterial thrombus causing loss of a cutaneous free flap at or beyond 6 months is a rare phenomenon. The purpose of this report is to describe 2 cases of arterial compromise requiring medical and surgical intervention at or beyond 6 months after radial forearm free flap (RFFF) phalloplasty and to define the phenomenon of ultradelayed arterial thrombosis. Methods: Patient 1 is a 44-year-old transmale who presented with pulselessness, pallor, and hypersensitivity of his neophallus 10 years status post-RFFF phalloplasty using a saphenous vein interposition graft (SVIG) between the superficial femoral artery (SFA) and radial artery (RA). Patient 2 is a 35-year-old transmale who presented with similar complaints 6 months status post-RFFF phalloplasty with the same vascular connections as above. Results: Patient 1 was found to have an arterial thrombus distal to the SFA-SVIG anastomosis requiring catheter-directed thrombolysis with tissue plasminogen activator, resulting in partial loss limited to the distal three fourths of the shaft. Patient 2 was also found to have an arterial thrombus distal to the SFA-SVIG anastomosis requiring catheter-directed thrombolysis with tissue plasminogen activator and common femoral artery CFA-RA bypass, resulting in partial loss limited to the neoglans. Conclusions: Ultradelayed arterial thrombosis is a rare phenomenon requiring urgent intervention. The exact causes of this phenomenon, whether mechanical or physiological or both, have yet to be fully elucidated but it is hypothesized that the original anastomosis may continue to serve as the critical blood supply to its flap as far as 10 years after surgery.